2022
DOI: 10.3390/life12101463
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 Italian Lockdown on Maxillofacial Trauma Related to Domestic Violence: A Retrospective Cohort Study

Abstract: Background: This retrospective study aims to identify the potential reasons for the increase in maxillofacial trauma from domestic violence in the first COVID-19 lockdown and propose some strategies that could be effective in fighting it during any future pandemic events. Materials and Methods: The study was conducted on patients with maxillofacial trauma who arrived at the Maxillofacial Unit of the Magna Graecia University of Catanzaro from 9 March to 3 May 2020, who were compared with those registered in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…However, in 2019-2020 there was a reversal of the etiological trend with 31.8% of trauma due to aggression compared to 6% recorded in previous years. During the 2020 lockdown, most traumas occurred in a domestic environment (75% in 2020 vs. 23.33% in 2019), particularly interpersonal violence in women (31.58% in 2020 vs. 14.28% in 2019) [17]. This reversal of the etiological trend was also highlighted in the Campania and Umbria regions [18][19].…”
Section: Discussionmentioning
confidence: 99%
“…However, in 2019-2020 there was a reversal of the etiological trend with 31.8% of trauma due to aggression compared to 6% recorded in previous years. During the 2020 lockdown, most traumas occurred in a domestic environment (75% in 2020 vs. 23.33% in 2019), particularly interpersonal violence in women (31.58% in 2020 vs. 14.28% in 2019) [17]. This reversal of the etiological trend was also highlighted in the Campania and Umbria regions [18][19].…”
Section: Discussionmentioning
confidence: 99%
“…A possible effect during the most severe moments of the pandemic was the lower willingness to seek medical attention in subacute maxillofacial processes (such as precancerous lesions, cancer, or infections) and the prognostic implication that this implied [30,37]. The availability of adequate protective material and understanding the route of contagion of COVID-19 have made it possible to treat fractures in a similar way in the pandemic and prepandemic periods, with various limitations by country in the most severe peaks of the pandemic [38][39][40][41][42]. In the postpandemic period, various studies have found that health professionals reduced their protective measures [38] due to burnout or psychological reasons, among others.…”
Section: Discussionmentioning
confidence: 99%